2007
DOI: 10.1177/0306624x07307783
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Employability of Ex-Prisoners and Offenders

Abstract: A large-scale study was conducted to examine the perceived employability of ex-prisoners and offenders. Four participant groups comprising 596 (50.4%) employers, 234 (19.8%) employment service workers, 176 (14.9%) corrections workers, and 175 (14.8%) prisoners and offenders completed a questionnaire assessing the likelihood of a hypothetical job seeker's both obtaining and maintaining employment; the importance of specific skills and characteristics to employability; and the likelihood that ex-prisoners, offen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
129
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(135 citation statements)
references
References 8 publications
3
129
3
Order By: Relevance
“…These factors relate to various characteristics relevant to the exoffender and their criminal history, as well as the employer and the organisational-context within which they work (Albright & Denq, 1996;Atkin & Armstrong, 2013;Graffam et al, 2008;Lukies, et al, 2011). Contributing further to the current body of literature, this paper aimed to apply the theoretical tenets of impression formation to examine the association between employers' willingness to hire job applicants with a criminal record and belief in redeemability, and whether individuating signals of desistance mediated this association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors relate to various characteristics relevant to the exoffender and their criminal history, as well as the employer and the organisational-context within which they work (Albright & Denq, 1996;Atkin & Armstrong, 2013;Graffam et al, 2008;Lukies, et al, 2011). Contributing further to the current body of literature, this paper aimed to apply the theoretical tenets of impression formation to examine the association between employers' willingness to hire job applicants with a criminal record and belief in redeemability, and whether individuating signals of desistance mediated this association.…”
Section: Discussionmentioning
confidence: 99%
“…These include the type and severity of the crime committed, number of previous convictions, and length of time spent in prison, since release or since their most recent offence (Albright & Denq, 1996;Atkin & Armstrong, 2013;Fahey, Roberts & Engel, 2006;Graffam, Shinkfield & Hardcastle, 2008; Kurlychek, Brame & Bushway, 2006). Employers also anticipate poor physical and/or mental health, as well as substance abuse issues may negatively impact work performance (Holzer, Raphael & Stoll, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that many inmates lack community living skills that are necessary for successful community reintegration [5]. A study by Graffam et al [6] discussed the employability of the ex-offenders and prisoners. From their study it was found that the above mentioned population was less likely to obtain and maintain employment than other disadvantaged groups (example physically disabled).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to [6] obtaining and maintaining employment is viewed as being very important for the successful re-integration of exoffenders in communities [7], also state that one of the main problems ex-offenders faced when returning home was an inability to sustain stable employment or inadequate positive support systems. It could be argued that the resettlement process for ex-offenders into their communities is quite difficult as failure to find employment and any form of support from the community could result in ex-offenders struggling to adapt to their various occupational roles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The general prisoner population are greatly at risk of social disadvantage and poor health outcomes, including a high risk of death during transition from prison . Of immediate concern on release for most prisoners is the need for stable housing and to find and maintain employment (Baldry, McDonnell, Maplestone, & Peeters, 2006;Graffam, Shinkfield, & Hardcastle, 2008;Shinkfield & Graffam, 2009;Travis, Solomon, & Waul, 2001). People with mental illness, and particularly those with co-occurring substance use disorder, typically have all of these problems with the addition of complex health needs, often accompanied by limited coping strategies (Draine, Wolff, Jacoby, Hartwell, & Duclos, 2005;Fisher, Silver, & Wolff, 2006).…”
Section: Introductionmentioning
confidence: 99%